DETERMINATION OF SOME HEAVY METALS CONCENTRATIONS FROM TOP SOIL OF METALS SCRAP YARDS AND THEIR CORRESPONDING CONTROL AREAS WITHIN GOMBE METROPOLIS, GOMBE STATE, NIGERIA, USING ATOMIC ABSORPTION SPECTROMETRY - S. ABDULSALAM,; A.D.BAJOGA,; H.A.DALA, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The analysis of heavy metals in soil samples collected was done using Atomic Absorption Spectrometer (AAS) model: Buck-205. The soil samples were air-dried to remove the moisture content. One gram (1 g) each of the soil samples was weighed, and then digested with aqua regia a mixture of concentrated hydrochloric acid and concentrated nitric acid in ratio 3:1 with continuous addition until the solution became pale yellow. The mixture was heated slowly and steadily on a hot plate by using a fume chamber and evaporated to about 50ml, then colored solution appeared colorless, then samples were cooled and analysed. The concentrations of heavy metals determined are in ppm Mn (41.022±9.712), Mg (15.00±2.806), Cu (4.416±1.511), Pb (2.685±0.442), Cr (0.460±0.084), Cd (0.125±0.019) and Co (0.04), whereas, the concentrations of Ni was not detected in all samples. However the comparison of the concentrations of the trace elements (Mn> Mg > Cu >Pd> Cr > Cd > Co) in the study area have shown that the metal scrap yard has impact in the presence of trace elements in soil. Hence concentrations of the metals in the sampling locations were greater than those determined in their control areas.